2013
DOI: 10.3390/molecules18033577
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Evaluation of 3-(2-Aminoheterocycle)-4-benzyloxyphenylbenzamide Derivatives as BACE-1 Inhibitors

Abstract: Three series of 3-(2-aminoheterocycle)-4-benzyloxyphenylbenzamide derivatives, 2-aminooxazoles, 2-aminothiazoles, and 2-amino-6H-1,3,4-thiadizines were designed, synthesized and evaluated as β-secretase (BACE-1) inhibitors. Preliminary structure-activity relationships revealed that the existence of a 2-amino-6H-1,3,4-thiadizine moiety and α-naphthyl group were favorable for BACE-1 inhibition. Among the synthesized compounds, 5e exhibited the most potent BACE-1 inhibitory activity, with an IC 50 value of 9.9 μΜ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…[298][299][300][301][302][303][304][305][306] The corresponding sulfur containing heterocycles, such as aminothiadiazines, have also been investigated. 307 Compound 140 (Fig. 63) showed an IC 50 of 9.9 mM.…”
Section: (E) Aminothiazoline-and Aminooxazoline-based Inhibitorsmentioning
confidence: 98%
See 1 more Smart Citation
“…[298][299][300][301][302][303][304][305][306] The corresponding sulfur containing heterocycles, such as aminothiadiazines, have also been investigated. 307 Compound 140 (Fig. 63) showed an IC 50 of 9.9 mM.…”
Section: (E) Aminothiazoline-and Aminooxazoline-based Inhibitorsmentioning
confidence: 98%
“…307 Compound 140 (Figure 63) showed an IC 50 of 9.9 μM. A modeling study showed that the naphthylbenzylamide extends into the S3 site while the amino group hydrogen bonds to Asp32 and Gly34.…”
Section: Nonpeptide Inhibitorsmentioning
confidence: 99%